If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5687 = 47(p + 40) Reorder the terms: 5687 = 47(40 + p) 5687 = (40 * 47 + p * 47) 5687 = (1880 + 47p) Solving 5687 = 1880 + 47p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-47p' to each side of the equation. 5687 + -47p = 1880 + 47p + -47p Combine like terms: 47p + -47p = 0 5687 + -47p = 1880 + 0 5687 + -47p = 1880 Add '-5687' to each side of the equation. 5687 + -5687 + -47p = 1880 + -5687 Combine like terms: 5687 + -5687 = 0 0 + -47p = 1880 + -5687 -47p = 1880 + -5687 Combine like terms: 1880 + -5687 = -3807 -47p = -3807 Divide each side by '-47'. p = 81 Simplifying p = 81
| 5s-7=-10+4s | | 17-(-4)= | | .06x+x=6895 | | 17-(-4)-4= | | (3x)2-10/4=54 | | 10r=80 | | 7v^2-40v-63=0 | | -25+x=-1225 | | 2x+28=x+40 | | 4/x-5=7-3/x-5 | | .4x+.5y=162 | | 3x-2(0)= | | x/3-24=-18 | | 4x+5y=162 | | 9x=-43+88 | | -14m-8=52 | | 2(3r-6)=4(r+2) | | x^2-6x+9-4y^2=0 | | (-6+3v+3x)(-2)= | | 3(0)-2=6 | | 12n=(11n)/19 | | (2x)+90=48 | | -1.5=-6/x | | 2x-22=x+3 | | 6(6v+7)-5=1+6v | | 9a-2(3a-6)=12 | | -7x+15x^2=20x | | 207=47x+-28 | | 12n=11n/19 | | 44=-6+m | | 52=x(1-x)x | | (5x-6)(2-x)=0 |